Epidural analgesia and the risk of operative delivery among women at term: A propensity score matched study. (September 2022) - Fieni, S.; di Pasquo, E.; Formisano, D.; Basevi, V.; Perrone, E.; Ghi, T.
Highlights: Epidural analgesia is considered the most effective method for pain relief during labor. Epidural analgesia may have direct and indirect effects on the progress of labor. An association between epidural anaesthesia and an increased risk of requiring operative delivery has been described. After matching for maternal and neonatal characteristics, this risk appears to be almost half of what has been previously reported. Abstract: Objective: To investigate the correlation between epidural analgesia (EA) administered during labour and the risk of requiring an operative delivery (caesarean section or operative vaginal delivery). Methods: This was a retrospective, multicentric cohort study. All singleton births of viable foetuses in cephalic presentation with a gestational age ≥ 37 weeks delivered between 2016 and2019 were included. A propensity score (PS) matching analysis was used to obtain comparable groups, balancing the maternal and pregnancy characteristics that required epidural analgesia during labour. The risk of operative delivery in women with and without epidural analgesia was estimated following PS-matching analysis (1:1 ratio). Results: As per the unmatched analysis, the occurrence of Caesarean section (CS) was significantly higher in women administered EA compared with the non-EA group (14.0 % vs 5.0 %; p < 0.001). The incidence of operative vaginal delivery (OVD) (9.1 % vs 4.0 %; p < 0.001) showed a similar pattern. The PS algorithm matched 16.301 cases who were administered EA with 16.301 cases not administered EA and found a significantly increased risk of CS (OR, 1.6; 95 %CI 1.5–1.7) and OVD (OR, 1.2; 95 % CI 1.1–1.2) in the former group. Conclusion: The risk of operative delivery almost halved in the EA group compared with the non-EA group, compared with the baseline risk of the unmatched subjects.